Influence social media on the implementation of public relations in selected higher learning institutions in northern Tanzania - Yategana Sing’ambi, Athanas; Andrew Lamu Amos, Amembah; Bhoke Africanus, Agnes (British Journal of Marketing Studies, 2020)
The paper assessed the influence of social media on the implementation of public relations. Research approaches were quantitative and qualitative research (explanatory correlation and case study designs). Simple random sampling, purposive and stratified sampling procedures were used to select University staff and students The target population was higher learning institutions in Northern Tanzania.  Quantitative data was analysed using descriptive and inferential statistics. Data was anlaysed through frequencies, percentages, means and narratives. The study had two hypotheses which were tested using independent t-test analysis. Both null hypotheses were rejected and alternative hypotheses were stated. The  findings showed that majority of respondents agreed that social media is a significant tool in influencing public relations programmes towards improving stakeholders relations in higher learning institutions. The study recommended that public relations managers and communication officers in the organization should increase and improve utilization of social media for the success of their communication strategies in the institution.